Legal Protection of Trademarks That Have Similarities In Principle In The Trademark Registration Process Is Associated with The Principle of Good Faith - Yuanda, Eryanto Pangaftu; Sahputra, Rilawadi; Sitompul, Ariman (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2024)
How the legal protection of brands that have similarities in essence on the trademark registration process is associated with the principle of good faith, as well as how the implementation of the provisions of equality in essence on trademark disputes and the consideration of judges in deciding the dispute is associated doctrine of Nearly Resembles (case study Supreme Court Decision No. 606.k / pdt.sus-HKI/2018). Research methods, this type of research is normative, descriptive research, taken from secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques with library studies / documentation studies. This study uses qualitative analysis.The result of this research is 2. Legal protection is carried out starting from the application, examination, and announcement, in the end the registrant meets the administrative requirements and the examination of the brand substancResearch methods, this type of research is normative, descriptive research, taken from secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques with library studies / documentation studies. This study uses qualitative analysis.The result of this research is 2. Legal protection is carried out starting from the application, examination, and announcement, in the end the registrant meets the administrative requirements and the examinatiaw.